Farmers' perception about variety development and abiotic stresses on potato cultivation in Bangladesh - Monayem Miah, M.A.; Hossain, T.M.B.; Hossain, S.; Kadian, M.S.; Hossain, M. (Bangladesh Academy of Sciences, 2013)
The socio-economic information on variety development and abiotic stresses of potato cultivation at farm level are scarce in Bangladesh. Therefore, an attempt was made to assess farmers perceptions about variety development and different abiotic stresses on potato cultivation. Primary data were collected from 240 potato farmers of Bogra and Chittagong district. The study revealed that Granula, Cardinal, and Lalpakri were the most preferred potato varieties in Bogra, while Diamant and Dohazari were the dominant varieties in Chittagong. Most farmers (70.87%) believe that the current potato yield (21.5-22.67 t/ha) can be further increased through introducing new HYVs. Drought and heat were two important limiting factors towards achieving the higher levels of potato yield. High yielding ability was considered as the most desirable varietal character and this was opined by almost 92.1% respondents, followed by drought resistant (61.13%), proper late blight control (58.75%), availability of adequate fund (57.77%), heat tolerant (53.60%), early maturity (61.5%), and good demand (44.5%) for HYV potatoes, whereas good test (81.7%), higher price (69.6%) and good storability (65.2%) were reported for local varieties. Low yield, susceptible to diseases, late maturity and low demand were the reasons for abandoning some potato varieties in the past. Dohazari variety for Chittagong and Lalpakri for Bogra have higher levels of tolerance against abiotic stresses. Finally, early maturity followed by drought tolerance, heat tolerance, and salinity tolerance were important attributes farmers wanted in new potato varieties. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16926 Bangladesh J. Agril. Res. 38(3): 401-416, September 2013